THE ROLE AND CONTRIBUTION OF MILITARY FIELD HOSPITALS IN ENSURING THE HEALTH SECURITY OF MILITARY PERSONNEL - Amgalanbaatar Davaadorj (International Journal of Innovative Technologies in Social Science, 2025)
This article explores the importance of military field hospitals in safeguarding the health and well-being of Armed Forces personnel, the optimal organization of their provision, and a comparison of international practices with the current situation in our country. Effectively organizing the provision of military field hospitals is a multifaceted endeavor that is a global concern, encompassing various organizational, technical, and human elements. While countries approach this issue with their unique experiences, tactical strategies, and technological advancements, there are common trends, technological solutions, and organizational principles that have been adopted by many nations. Research shows that effective field hospital operations have a significant impact on combat readiness, with studies indicating that providing primary medical care within one hour can increase survival rates to over 85 percent. The article examines the hierarchical structure of field medical care from Role I (tactical combat first aid) to Role IV (permanent hospital transfer), looking at successful implementations by NATO forces, the US Army, Israeli Defense Forces, and lessons learned from recent conflicts. The experiences of the Mongolian Armed Forces’ field hospitals in international peacekeeping missions and domestic emergency responses are assessed against global standards. Key findings suggest that modern military field hospitals need modular design, rapid deployment capabilities, advanced technological integration including drone support, and comprehensive logistics coordination. The study concludes that while Mongolia has shown operational competence in various international missions, significant improvements in equipment modernization, personnel training systems, and logistical infrastructure are necessary to meet contemporary military medical standards and ensure optimal health security for military personnel.